2019
DOI: 10.1002/smll.201900982
|View full text |Cite
|
Sign up to set email alerts
|

Dark‐Exciton‐Mediated Fano Resonance from a Single Gold Nanostructure on Monolayer WS2 at Room Temperature

Abstract: carried out to explore Fano resonances that arise from the coupling between surface plasmons (SPs) and excitons in quantum dots (QDs) or dye molecules. [2,[6][7][8][9][10][11] However, the lack of efficient ways to actively tune the excitonic properties of QDs and dye molecules near plasmonic nanostructures makes the development of active devices based on hybrid plasmon-QD/ dye systems challenging. Recently, the interaction between plasmonic nanostructures and emerging 2D semiconductors, including monolayer tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 54 publications
(116 reference statements)
2
50
0
Order By: Relevance
“…Recent studies have successfully demonstrated strong coupling effect at the single nanoparticle level by using semiconducting transition metal dichalcogenide (TMDC) layers, [ 30–35 ] quantum dots (QDs), [ 36 ] molecules, [ 37–41 ] perovskite nanowires, [ 42 ] and TMDC nanodisks. [ 43 ] Due to the lack of efficient ways to control the excitonic orientation of molecules and QDs, the exciton‐plasmon coupling relies on the change of surface plasmon resonance or the polarization of the incident light.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have successfully demonstrated strong coupling effect at the single nanoparticle level by using semiconducting transition metal dichalcogenide (TMDC) layers, [ 30–35 ] quantum dots (QDs), [ 36 ] molecules, [ 37–41 ] perovskite nanowires, [ 42 ] and TMDC nanodisks. [ 43 ] Due to the lack of efficient ways to control the excitonic orientation of molecules and QDs, the exciton‐plasmon coupling relies on the change of surface plasmon resonance or the polarization of the incident light.…”
Section: Introductionmentioning
confidence: 99%
“…2D materials, such as graphene and transition metal dichalcogenides (TMDCs), have attracted incredible interest because of their extraordinary properties that make them promising candidates for next generation electronic and optoelectronic applications. [ 1–10 ] In contrast to graphene, TMDCs are semiconducting materials with layer‐dependent bandgap in the range of 1−2 eV, [ 11,12 ] exhibiting rich novel fundamental physical properties and promising applications in electronics and optoelectronics. [ 13–16 ] In spite of the attractive photoresponse performances, most of photodetectors based on TMDCs only show photoresponse in visible range, [ 17–19 ] which seriously hinder their real applications.…”
Section: Introductionmentioning
confidence: 99%
“…Resonance. [39] Besides plasmon-2D semiconductors , [27,28] applications in other plasmon-exciton coupling systems, such as plasmon-quantum dots [40,41] and plasmon-dye molecules systems, [42] have also been investigated.…”
Section: Doi: 101002/smll202003539mentioning
confidence: 99%